Interaction Model of the Interface Nasicon with Aqueous Solution - Nga, Nguyen Tuyet; Son, Vo Thach; Deslouis, C. (Communications in Physics, 2008)
Complex impedance spectroscopy (CIS) study was carried out using the 4-electrodes cell arrangement with NASICON membrane. The physical model developed in this work was based on own CIS characteristic of the system NASICON/solution, and it accurately described the experimental diagrams. The electronic parameters could be determined from the fittings with the designed model.